China's power and Asian security - Li, Mingjiang; Kemburi, Kalyan M. (Abingdon, Oxon : Routledge, 2015)
'One of the most significant factors for contemporary international relations is the growth of China's economic, military, and political power. Indeed, few analysts would dispute the observation that China's power has strongly influenced the structure of the international system, major-power strategic relations, international security, the patterns of trans-border economic activities, and most importantly, the political and security dynamics in Asia in the twenty-first century. This book maps the growth of China's political, economic, and military capabilities and its impact on the security order in Asia over the coming decades. While updating the emerging power dimensions and prevailing discourse, it provides a nuanced analysis of whether the growth of Chinese power is resulting in Beijing becoming more assertive, or even aggressive, in its behavior and pursuit of national interests. It also examines how the key Asian countries perceive and react to the growth of China's power and how US rebalancing would play out in the context of Beijing's political, economic, and military power. China's Power and Asian Security will be of huge interest to student and scholars of Asian politics, Chinese politics, security studies and international security and international relations more generally'--
1. Growth of China's power : capabilities, perceptions, and practice / Mingjiang Li, Kalyan Kemburi, and Zhang Hongzhou -- 2. The rise of China and the emerging order in Asia / Jingdong Yuan -- 3. China's military buildup : regional repercussions / Richard A. Bitzinger -- 4. China's assessments of U.S. rebalancing/pivot to Asia / Wang Dong and Yin Chengzhi -- 5. China's rising power and the U.S. rebalance to Asia : implications for U.S.-China relations / Phillip C. Saunders -- 6. Peripheral South Asian response to the growth of Chinese power : a study in Dichotomous continuity / Mahmud Ali -- 7. India's perceptions and responses to the growth of Chinese power / Rajeswari Pillai Rajagopalan -- 8. Canberra's Beijing balance : Australian perceptions of and responses to Chinese power / Rory Medcalf -- 9. Facing the challenges : ASEAN's institutional responses to China's rise / Kai He -- 10. Evaluating Southeast Asian responses to China's rise : the vital context of managing great power resurgence / Evelyn Goh -- 11. China-Central Asia : a new economic, security, and logistic network / Alessandro Arduino -- 12. China's challenges in accommodating both Koreas / Choo Jaewoo -- 13. The rise of China and Japan's foreign policy reorientation / Ken Jimbo -- 14. The changing security dynamics in Northeast Asia and the US alliances with Japan and South Korea : toward synchronization / Hiroyasu Akutsu.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Security, International -- Asia; China -- Foreign relations -- 21st century; China -- Economic conditions -- 2000-; China -- Foreign economic relations; China -- Military policy; China -- Foreign relations -- Asia; Asia -- Foreign relations -- China; Electronic books